Data Mining Pengelompokan Akta Nikah Berdasarkan Usia Nikah atau Domisili Menggunakan Metode Clustering: Studi Kasus Kemenag Langkat - Nurlaila, Nurlaila; Buaton, Relita; Saragih, Rusmin (Sci-tech Journal, 2023)
One way to find out the marriage certificate data is to group the prospective bride and groom data that has been recorded at the Langkat Ministry of Religion. The analysis was carried out using the Clustering method using the K-Means method which was translated into a software. This software is used for grouping data. The output is to find out the grouping of marriage certificate data with the closest relationship between the age group of the groom, occupation and address. The results showed that the age of the groom-to-be between 19-28 years old had a civil servant job at the address/district of Kutambaru. Keywords: age, occupation, address/location and clustering